Antimicrobial Resistance - A Global Threat 2019
DOI: 10.5772/intechopen.79371
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Poultry Production and Its Effects on Bacterial Resistance

Abstract: A surge in the development and spread of antibiotic resistance has become a major cause for concern. Over the past few decades, no major new types of antibiotics have been produced and almost all known antibiotics are increasingly losing their activity against pathogenic microorganisms. The levels of multi-drug resistant bacteria have also increased. It is known that worldwide, more than 60% of all antibiotics that are produced find their use in animal production for both therapeutic and non-therapeutic purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
167
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(218 citation statements)
references
References 91 publications
(100 reference statements)
11
167
2
2
Order By: Relevance
“…Currently, it is estimated that 60% production of all the antimicrobial agents is used in livestock including poultry. Although use of these agents has improved poultry performance effectively and economically, it has also resulted in the development of the antimicrobial-resistant strains of pathogenic bacteria which ultimately creating serious public health concerns via food chain (Agyare et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is estimated that 60% production of all the antimicrobial agents is used in livestock including poultry. Although use of these agents has improved poultry performance effectively and economically, it has also resulted in the development of the antimicrobial-resistant strains of pathogenic bacteria which ultimately creating serious public health concerns via food chain (Agyare et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although these two antibiotics were considered to have a lower risk and are most commonly used on chicken farms worldwide [20,21,24], frequent and regular use can accelerate the resistance process [5,25]. Previous studies have reported high rates of resistance to amoxicillin and oxytetracycline in poultry in China and other countries [11,26,27]. This eventually leads farmers to use higher level of medically important antibiotics or other antibiotics on the prohibited list [28,29].…”
Section: Famers' Practice Of Antibiotic Usementioning
confidence: 99%
“…Poultry refers to the breeders and production animals of broilers, chickens, and turkeys. Chicken is the most frequently farmed spp., producing more than 90 billion tons of chicken meat per year (Agyare et al, 2018). Most countries use a wide variety of (Sahoo et al, 2010;Landers et al, 2012;Boamah et al, 2016).…”
Section: Use Of Antimicrobials In Poultrymentioning
confidence: 99%